Reclaiming the conversation : Islamic intellectual tradition in the Malay archipelago - Hashim, Rosnani (The Other Press, 2010)
This book brings together writings by academics from around the region highlighting the efforts of eleven Malay-Muslim educational reformers, and examines the debates that took place on this crucial topic. It aims to show that these scholars were not only teachers of religion, but were those imbued with deep knowledge in both the 'worldly' and 'religious' sciences, and committed both to engaging with the challenges their societies faced at the time and reviving the intellectual tradition among the Malay intelligentsia. As such, the essays in this book represent an effort to revive the discourse initiated by these scholars in the hope of stimulating and informing discussion on the problems faced in the region today.